Prevention Of Type 2 Diabetes Mellitus Among Adolescents In Ternate City, Indonesia - Didik Kurniawan; Ramli Ramli; Hamidah Rahman Rahman (Saintika Medika, 2021)
Complication of diabetes mellitus cause death. The death rate due to complication of diabetes mellitus was the third highest in Indonesia. Meanwhile, based on the data in 2009, people with type 2 diabetes mellitus (T2DM) in Kota Ternate was the third highest across Indonesia. In order to prevent an increase in T2DM sufferers, several strategies are needed, including prevention from an early age including in adolescents. The research aims to evaluate T2DM-related Knowledge, Attitudes, and Practices (KAP) of the adolescents in Ternate city, in order to obtain data as an illustration that can be utilized in the management of T2DM. The research design was a cross sectional study. The study population was 22,653 adolescents aged 15-19 years, with a sample of 394 adolescents. Data were obtained using a questionnaire to measure the level of KAP about diabetes mellitus, risk factors and diabetes mellitus prevention. Statistical data analysis using descriptive analysis. The conclusion obtained by the analysis of the answers to each KPA question. The results showed the majority of respondents were 15 years of age (32.5%), the dominant gender is female (59.9%), education is being taken is Senior High School (53.6%). The highest respondent's knowledge level was in good category (53.8%), the attitude of the most respondents was in good category (72.6%), while the prevention practice of T2DM was also in good category (76.4%). Even though KAP shows good results, there was still many questions and statements that were answered incorrectly by respondents. Therefore, it is suggested that more in-depth educational programs in order to be propagated, especially for adolescents, since education is one of the five pillars of containment procedures T2DM.